Peran dari Layanan Makerspaces dalam Kegiatan Komunitas Gerakan SUMUT Mengajar - Aini, Nurul; Purwaningtyas, Franindya (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
According to the Ministry of Trade of the Republic of Indonesia, the creative economy is an industry that originates from the use of individual creativity, skills and talents to create prosperity and employment opportunities through the creation and utilization of the individual's creativity and inventiveness. The creative economic activity carried out by a group of volunteers in Nagur Village, Tanjung Beringin District, Serdang Bedagai is making pencil boxes from used bottles. Makerspace activities in the North Sumatra Teaching Movement community activities have a role as an educational space, creation or creativity space, social space and academic introduction to early childhood. As an educational space and a space for creation or creativity, these are activities that almost all volunteer groups do, such as teaching the Koran, teaching elementary school and middle school children what they don't know. And in the creation or creativity space, volunteer groups also carry out activities such as making crafts from used materials. With the existence of a makerspace, those of us who have creative ideas or knowledge that we want to share with the wider community can channel it directly and use a building or place that can be repurposed as a makerspace.